(untitled) (Pulse, 2014)
Progressive Multifocal Leukoencephalopathy (PML) is a rare and usually fatal viral disease occurring almost exclusively in people with severe immune deficiency. This is a demyelinating disease of the central nervous system (CNS) that usually leads to death or severe disability. Patients usually present with focal CNS abnormalities like; hemiparesis, apathy, and confusion. Multifocal white matter lesions without mass effect lead to the diagnosis of PML. In this article we present a review of literature and report of a case of PML in which the patients clinical status and MR findings are typical. DOI: http://dx.doi.org/10.3329/pulse.v6i1-2.20355 Pulse Vol.6 January-December 2013 p.57-59